2011
DOI: 10.1603/en10244
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure and Spatial Influence of Agricultural Variables on Hessian Fly Populations in the Southeastern United States

Abstract: Population structure dictates the evolution of each population, and thus, the species as a whole. Incorporating spatial variables with population genetic statistics allows for greater discovery beyond traditional population genetics alone and can inform management decisions. The understanding of population structure in Hessian fly, Mayetiola destructor (Say), a pest of wheat, has been limited in the past. We scored 14 microsatellite loci from 12 collections of Hessian fly in the southeastern United States. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 79 publications
(81 reference statements)
4
6
0
Order By: Relevance
“…In the current study, however, a higher K value was found, further refining the population genetic structure in the southeastern US and providing similar results as the higher K values (e.g. K = 4) in Morton et al [54]. These results suggest divergence between different regions with a higher level of gene flow within a region.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In the current study, however, a higher K value was found, further refining the population genetic structure in the southeastern US and providing similar results as the higher K values (e.g. K = 4) in Morton et al [54]. These results suggest divergence between different regions with a higher level of gene flow within a region.…”
Section: Discussionsupporting
confidence: 88%
“…All collections fit into pseudo-regional populations, with the exception of FlSC and HoMS, which stood independently as their own population. With respect to the populations in the southeastern US, overall similar results were found previously [54]; however, the additional collections added to the resolution of the population genetic structure. For example, Morton et al [54] found K = 2 in the southeastern populations, although there was more structure when looking at a higher K value.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Microsatellites (SSRs) and SNPs have been used successfully to characterize populations in insects (Behura, ; Morton et al ., ). Microsatellites have the advantages of rapid evolution, frequently multiple alleles, and likely selective neutrality (Li et al ., ), but with these advantages come a high likelihood of evolutionary reversals (homoplasy) in allele size (van Zijll de Jong et al ., ) and problems in scoring the alleles accurately (Selkoe & Toonen, ).…”
Section: Introductionmentioning
confidence: 97%